From NOSQL databases to decision support systems: developing a business intelligence solution - Pereira, José Luís (2019)
We are living a time in which the data generated by humans and machines has reached levels never seen before the so-called era of Big Data. Everyday, vast amounts of data, coming from different sources and with different formats, are created and made available to organizations. First, with the rise of the social networks and, more recently, with the advent of the Internet of Things (IoT), data with enormous potential for organizations is being continuously generated. In order to be more competitive, organizations need to explore all the richness that is present in those data. Indeed, data is only as valuable as the insights organizations gather from it to make better decisions, which is the main goal of Business Intelligence (BI). In this paper, we describe the development of a decision support system in which data obtained from a NoSQL database is used to feed a BI solution.